Spectral and morphological signatures of cluster merger shocks: CIZA J2242.8+5301 - Stroe, Andra; Weeren, Reinout J van; Sobral, David; Rumsey, Clare; Intema, Huib; Röttgering, Huub JA; Harwood, Jeremy J; Saunders, Richard; Brüggen, Marcus; Hoeft, Matthias
The CIZA J2242.8+5301 cluster hosts an extraordinary, narrow, Mpc-wide, diffuse patch of radio emission tracing travelling shock waves, called a relic. We perform a multi-wavelength of observations of the cluster. We discover radio spectral steepening and increasing spectral curvature in the shock downstream area, indicative of emission produced by spectrally-aged electrons, following a JP ageing model. The curved integrated spectrum towards $16$ GHz challenges the favoured relic formation model. Further, we find a boosting the number density of H$α$ emitters by a factor of $10$, possibly caused by interactions of the galaxies with the shock wave.